Contemporary houses - Druesne, Alexandra; Pauwels, Jo (Enghien, Belgium : Beta-Plus, 2009)
Covers modern interiors, looking at the layout and trends in contemporary design.
engineering bookfair2015
Keywords: Interior decoration; Interior decoration -- History -- 21st century